PHOSPHATIDIC ACID PHOSPHOHYDROLASE Regulates Phosphatidylcholine Biosynthesis in Arabidopsis by Phosphatidic Acid-Mediated Activation of CTP:PHOSPHOCHOLINE CYTIDYLYLTRANSFERASE Activity - Craddock, Christian P. (Plant Cell, 2015)
Regulation of membrane lipid biosynthesis is critical for cell function. We previously reported that disruption of PHOSPHATIDIC ACID PHOSPHOHYDROLASE1 (PAH1) and PAH2 stimulates net phosphatidylcholine (PC) biosynthesis and proliferation of the endoplasmic reticulum (ER) in Arabidopsis thaliana. Here, we show that this response is caused specifically by a reduction in the catalytic activity of the protein and positively correlates with an accumulation of its substrate, phosphatidic acid (PA). The accumulation of PC in pah1 pah2 is suppressed by disruption of CTP:PHOSPHOCHOLINE CYTIDYLYLTRANSFERASE1 (CCT1), which encodes a key enzyme in the nucleotide pathway for PC biosynthesis. The activity of recombinant CCT1 is stimulated by lipid vesicles containing PA. Truncation of CCT1, to remove the predicted C-terminal amphipathic lipid binding domain, produced a constitutively active enzyme. Overexpression of native CCT1 in Arabidopsis has no significant effect on PC biosynthesis or ER morphology, but overexpression of the truncated constitutively active version largely replicates the pah1 pah2 phenotype. Our data establish that membrane homeostasis is regulated by lipid composition in Arabidopsis and reveal a mechanism through which the abundance of PA, mediated by PAH activity, modulates CCT activity to govern PC content.